Early diagnosis of progressive multifocal leucoencephalopathy: longitudinal lesion evolution. Issue 3 (2nd November 2018) - Scarpazza, Cristina; Signori, Alessio; Prosperini, Luca; Sormani, Maria Pia; Cosottini, Mirco; Capra, Ruggero; Gerevini, Simonetta
Abstract : Objective: Early diagnosis of natalizumab-related progressive multifocal leucoencephalopathy (NTZ-PML) in multiple sclerosis has been deemed a major priority by the regulatory agencies but has yet to become a reality. The current paper aims to: (1) investigate whether patients with NTZ-PML pass through a prolonged presymptomatic phase with MRI abnormalities, (2) estimate the longitudinal PML lesion volume increase during the presymptomatic phase and (3) estimate the presymptomatic phase length and its impact on therapy duration as a risk stratification parameter. Methods: All Italian patients who developed NTZ-PML between 2009 and 2018 were included. The data of patients with available prediagnostic MRI were analysed (n=41). Detailed clinical and neuroradiological information was available for each participant. Results: (1) PML lesions were detectable in the presymptomatic phase in 32/41 (78%) patients; (ii) the lesion volume increased by 62.8 % for each month spent in the prediagnostic phase; (3) the prediagnostic phase length was 150.8±74.9 days; (4) PML MRI features were detectable before the 24th month of therapy in 31.7 % of patients in our cohort. Conclusions: Considering the latency of PML clinical manifestation, the presymptomatic phase length supports the usefulness of MRI surveillance every 3–4 months. Early diagnosis could prompt a better outcome for patients due to the relationship between lesion volume and JC virus infection. The insight from this study might also have an impact on risk stratification algorithms, as therapy duration as a parameter of stratification appears to need reassessment.